Communicating the Past in the Digital Age Proceedings of the International Conference on Digital Methods in Teaching and Learning in Archaeology (12-13 October 2018) - Hageneuer , Sebastian (Ubiquity Press, 2020)
"Recent developments in the field of archaeology are not only progressing archaeological fieldwork but also changing the way we practise and present archaeology today. As these digital technologies are being used more and more every day on excavations or in museums, this also means that we must change the way we approach teaching and communicating archaeology as a discipline. This volume presents the outcome of a two-day international symposium on digital methods in teaching and learning in archaeology held at the University of Cologne in October 2018. Specialists from around the world share their views on the newest developments in the field of archaeology and the way we teach these with the help of archaeogaming, augmented and virtual reality, 3D reconstruction and many more. "